Pesca artesanal em Maracajaú-RN, Brasil: uma abordagem etnoecológica - Calado, Janaina Freitas (2010)
The artisanal fishery of Maracajaú, a community in Maxaranguape City, Rio Grande do Norte, Brazil, was characterized by an investigation both of the scientific knowledge and local ecological knowledge (LEK) of fishermen. The jangada was the kind of boat mostly utilized in the fishery. 83 fish species were utilized as fishery resoureces in the area. The majority of these resources are captured with hand line during the summer. The Guaiuba (Ocyurus chrysurus) was the most captured species during the whole study period, followed by the Espada (Trichiurus lepturus). An index of the fishery importance (IPP) was proposed in this study, in order to point out those species that possess biological, ecological, behavioral and commercial attributes that render them as valuable in the fishery community. Following the IPP criteria, seven species were highlighted in the studied community: Guaiuba (Ocyurus chrysurus), Espada (Trichiurus lepturus), Cioba (Lutjanus analis), Dentão (Lutjanus jocu), Cavala (Scomberomorus cavalla), Serra (Scomberomorus brasiliensis) and the Guarajuba (Carangoides bartholomaei). An ethnoecological study was conducted on these seven species and showed that the artisanal fishermen possess a detailed knowledge on the biology and ecology of the fishes, which is mostly coincident with the scientific knowledge and the field observations. Finally, it was observed that the LEK of the fishermen on the most important species for the fishery was greater than for the species considered less important. Such results confirm earlier studies in that the local knowledge of fishermen is a valuable tool and subsidy of fishery management plans. Such knowledge possesses attributes that qualify it both for complementing the scientific knowledge on the marine fish species, and to act as an instrument to promote the popular participation in the management of fishery resources.